Dietary Intervention with β-Lactoglobulin-Derived Peptides and a Specific Mixture of Fructo-Oligosaccharides and Bifidobacterium breve M-16V Facilitates the Prevention of Whey-Induced Allergy in Mice by Supporting a Tolerance-Prone Immune Environment - Kostadinova, Atanaska I.; Pablos-Tanarro, Alba; Diks, Mara A. P.; van Esch, Betty C. A. M.; Garssen, Johan; Knippels, Léon M. J.; Willemsen, Linette E. M. (Frontiers in Immunology, 2017)
Cow’s milk allergy (CMA) prevails in infants and brings increased risk of developing other allergic diseases. Oral administration of specific β-lactoglobulin (BLG)-derived peptides (PepMix) and a specific blend of short- and long-chain fructo-oligosaccharides and Bifidobacterium breve M-16V (FF/Bb) was found to partially prevent CMA development in mice. In this study, we aimed to expand the knowledge on the preventive potential and the underlying mechanisms of this approach. Three-week-old female C3H/HeOuJ mice were orally exposed to PepMix±FF/Bb prior to a 5-week oral sensitization with whole whey and cholera toxin as an adjuvant. The acute allergic skin response was determined after an intradermal challenge with whole whey protein. Following an oral challenge with whey, regulatory T cells (Tregs) in the small intestine lamina propria (SI-LP) and mRNA expression of immune markers in the Peyer’s patches (PP) were investigated. The early impact of PepMix and FF/Bb interventions on the immune system during the oral tolerance (OT) induction phase was investigated after the last OT administration. Pre-exposing mice to PepMix+FF/Bb partially prevented the acute allergic skin response compared to PBS and increased Tregs and activated T cells in the SI-LP compared to sham-sensitized mice. It also increased the mRNA expression of Tbet over GATA3 in the PP of whey-sensitized mice. Directly upon the 6-day OT phase, FF/Bb intervention enhanced cecal content levels of propionic and butyric acid in PepMix-fed mice and the former was positively correlated with Foxp3+ cell numbers in the colon. In the PP of PepMix+FF/Bb-exposed mice, IL-22 mRNA expression increased and IL-10 followed the same tendency, while the Foxp3 expression was increased over GATA3 and RorγT. In the colon, the Tbet mRNA expression increased over GATA3, while IL-22 decreased. In addition, the Foxp3+/GATA3+ and regulatory/effector T cell ratios in the mesenteric lymph nodes and the CD11b+/CD11b− conventional dendritic cells ratio in the SI-LP were increased. In conclusion, the FF/Bb diet facilitates the capacity of the specific BLG-peptides to partially prevent the allergic response after sensitization to whole whey protein, possibly by creating a tolerance-prone environment during the OT phase. Such a dietary intervention might contribute to tailoring successful strategies for CMA prevention.